Predictive factors of recurrence and malignant transformation in vocal cord leukoplakia - علي, مرح; يوسف يوسف; مصطفى ابراهيم (Latakia University Journal -Medical Sciences Series, 2024)
Objective: To identify antecedent risk factors for predicting vocal cord leukoplakia recurrence and malignant transformation. Materials and methods: The sample included 58 patients attending the Ear, Nose, and Throat Surgery Clinic at Tishreen University Hospital during the time period 2022-2023 with white lesions on the vocal cord and who met the inclusion criteria in the research. Their ages ranged from 35 to 77 years, with an average of 64.27 ± 6.8 years. All patients participating in the study were interviewed and the following information was recorded for each patient: name; Age, gender, habits and instincts (smoker, alcoholic); Then he took a comprehensive medical history from the patients, A comprehensive clinical examination of the head and neck was performed and the larynx was carefully examined with a laryngoscope. The morphological features of the lesion and its extension on the vocal cord were recorded. An initial clinical diagnosis was made. Then a tissue biopsy of the white lesion on the vocal cord was performed and sent to the pathological autopsy. After the results appeared, appropriate treatment), patients were monitored for 18 months, during which factors leading to leukoplakia recurrence and transformation into malignancy were identified. Results:The study showed that the smoking and the degree of dysplasia and the extent of the lesion extending over the vocal cord have a significant statistical significance in the recurrence of vocal cord leukoplakia and its transformation into malignancy. Conclusions:The patient should be informed of the possibility of leukoplakia reoccurring and becoming malignant if the patient is a smoker, and/or has vocal cord leukoplakia with a lesion of more than half of the vocal cord and/or moderate or severe dysplasia on histological biopsy result.